Persistence of de novo donor‐specific HLA‐antibodies after lung transplantation: A potential marker of decreased patient survival. (18th July 2018) - Schmitzer, M.; Winter, H.; Kneidinger, N.; Meimarakis, G.; Dick, A.; Schramm, R.; Klotz, L. V.; Preissler, G.; Strobl, N.; von Dossow, V.; Schneider, C.; Weig, T.; et al.
Abstract : The impact of de novo donor‐specific anti‐HLA‐antibodies (donor‐specific antibody [DSA]) on outcomes in lung transplantation is still a matter of debate. We hypothesize that differentiating DSA by persistent and transient appearance may offer an additional risk assessment. The clinical relevance of HLA‐antibodies was investigated prospectively in 72 recipients with a median follow‐up period of 21 months. The presence of HLA‐antibodies was analysed by a single antigen bead assay before and after (3 weeks, 3, 6, 12 and 18 months) transplantation. In 23 patients (32%), de novo DSAs were detected. In 10 of these patients (44%), DSA persisted throughout the follow‐up period, whereas 13 of these patients (56%) had transient DSA. There was a trend towards lower 1‐year‐survival in DSA‐positive compared with DSA‐negative patients (83% vs 94%; P = 0.199). Remarkably, patients with persistent DSA had significantly reduced survival (1‐year survival 60%) compared with both patients without DSA and those with transient DSA ( P = 0.005). Persistent DSA represented as an independent prognostic factor for reduced overall survival in multivariate analysis (HR 8.3, 95% CI 1.8‐37.0; P = 0.006). Persistence of DSA during the first year after transplantation seems to be more harmful for lung allograft function than transiently detected DSA at an early stage.